Comparison of AlGaN p–i–n ultraviolet avalanche photodiodes grown on free-standing GaN and sapphire substrates. (9th November 2015) - Kim, Jeomoh; Ji, Mi-Hee; Detchprohm, Theeradetch; Dupuis, Russell D.; Ryou, Jae-Hyun; Sood, Ashok K.; Dhar, Nibir D.; Lewis, Jay
Abstract: We compare the performance characteristics of Al0.05 Ga0.95 N UV avalanche photodiodes (APDs) grown on different substrates. UV-APDs grown on a free-standing GaN substrate show lower dark-current densities for all fabricated mesa sizes than similar UV-APDs grown on a GaN/sapphire template. In addition, a stable avalanche gain higher than 5 × 10 5 and a significant increase in the responsivity of UV-APDs grown on a free-standing GaN substrate are observed. We believe that the high crystalline quality of Al0.05 Ga0.95 N UV-APDs grown on a free-standing GaN substrate with low dislocation density is responsible for the observed low leakage currents, high performance characteirstics, and reliability of the devices.